Outcome of neonates born to mothers with pregnancy induced hypertension/preeclampsia: a systematic review - Arulparithi, C. Subramanian; Manjani, Sekar; Prakash, Petchimuthu (International Journal of Contemporary Pediatrics, 2023)
Preeclampsia affects 3-10% of pregnancies worldwide. It has significant adverse effect on both the fetus and the neonate. Hence there is a need to study the impact of pregnancy induced hypertension (PIH) on the fetus and the neonate. Databases like PubMed and Cochrane are searched independently by two authors to identify relevant studies. Data were collected for outcomes like birth weight, gestational age, fetal death/stillbirth and intrauterine growth retardation (IUGR). Preeclampsia is associated with significant increase in the incidence of low birth weight (LBW), IUGR and prematurity compared to normotensive women. Also, there is an increased rate of fetal death/ stillbirths in preeclampsia. In addition, there is an increased need for neonatal intensive care unit (NICU) admission in neonates born to PIH mothers. Maternal preeclampsia results in significant adverse effect on the fetus and neonate. There is an increased incidence of stillbirth, LBW, IUGR and preterm deliveries in neonates born to preeclamptic mothers. There is an overall increase in the composite outcomes of neonates of PIH mothers. The objective of the study is to compare the neonatal outcomes of preeclamptic or women with gestational hypertension with that of normotensive women.